Perkembangan Akuntansi Keuangan Serta Tantangan di Era Digital - adin, Farhan Adin Saputra; OKta, Okta Adi Saputra; Adib, Adib Asyraf; Ratih Kusumastuti (CV. Kalimasada Group, 2023)
Writing this article aims to find out the development of Financial Accounting as well as challenges in the digital era. Along with the increasingly complex business environment, the demands of Financial Accounting for transparency and accountability are increasing. This encourages participation and what is the role of financial accounting and what are the challenges in this digital era as the reliability of a financial report. In this article, we review several objective literature reviews as a reference for the study. This article also discusses the history of financial accounting in the world and in Indonesia, and the challenge is the lack of understanding of technology by financial managers which affects the performance and effectiveness of their positions so that people who are competent in the field of accounting may be replaced by people who are competent in the field of technology and then day.